Konsep Kerja Sama (Syirkah) dalam Bisnis Islam Menurut Perspektif Hadis - Mukhoniadi, Risman (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2023)
The purpose of this study is to examine and understand more deeply about what Syirkah (cooperation) is contained in the letter Shaad verse 24. This research is a library research using literature (library) as a source, including books of interpretation and supporting scientific articles. On the other hand, the interpretation method used in this research is the maudu'i (thematic) method and the tahlili (analytic) interpretation method. The literature used comes from the Qur'an, hadith and opinions from madhhabs and Islamic jurists. The occurrence of economic stagnation often occurs because the owners of capital are not able to manage their own capital or vice versa have the ability to manage capital but do not have the capital, this can be solved in syirkah which is justified in Islamic sharia. Based on this research, it can be concluded that the syirkah model is a concept that can precisely solve capital problems. On the one hand, Islamic principles state that everything that is used by others is entitled to mutually beneficial compensation, whether for capital goods, labor or rental goods. On the other hand, Islam firmly rejects compensation for capital goods in the form of interest.